Electoral volatility and strategy of Federal Congressmen - Guerreiro, Julia Mantovani (2017)
This dissertation focuses on conciliating two apparently contradictory facts: a fall in electoral volatility and a high turnover rate in the Chamber of Deputies. We use the case of Brazil and explore the hypothesis that politicians will use the advantages resulting from the fall in electoral volatility rates in different ways, depending on the type of party to which they belong. It is assumed that the decrease in volatility is greater in more institutionalized parties and for the incumbents of these parties. Given that institutionalized parties are able to provide clearer information, which helps incumbents improve their electoral strategies, the reasons for their defeats – whether due to intraparty or interparty competition – will vary according to their party’s level of institutionalization.